2022
DOI: 10.1097/jcma.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired infections in patients hospitalized with COVID-19: First report from Taiwan

Abstract: Background: Coronavirus disease 2019 (COVID-19) inpatients may acquire infections from other pathogens during hospital admission. This is the first research on this subject to be reported from Taiwan. Methods: Confirmed COVID-19 inpatients were enrolled in this study from January 1, 2020 to July 31, 2021. Various types of pathogens in COVID-19 inpatients, with hospital-acquired infections, were identified and analyzed. The clinical characteristics of COVID-19 patients with and without hospital-acquired infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The detailed screening process is available in Figure 1. Finally, 32 articles were included in our systematic review 15,18–48 . The characteristics of included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed screening process is available in Figure 1. Finally, 32 articles were included in our systematic review 15,18–48 . The characteristics of included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The most common disease entity for both pathogens is lower respiratory tract infections. During [53]. Another study in Qatar investigated risk factors for the isolation of multidrug-resistant (MDR) Gramnegative bacteria from critically ill COVID-19 patients.…”
Section: Key Pointsmentioning
confidence: 99%
“…Acinetobacter spp. (19/88, 21.6%) were the most frequently isolated bacteria, and S. maltophilia (14/88, 15.9%) was second [53]. Another study in Qatar investigated risk factors for the isolation of multidrug-resistant (MDR) Gram-negative bacteria from critically ill COVID-19 patients.…”
Section: Risk Factors and Clinical Presentations Of Stenotrophomonas ...mentioning
confidence: 99%
“…The increasing incidence of S. maltophilia infections has been highlighted during the COVID-19 epidemic [ 10 ]. Recent studies have shown increased prevalence of S. maltophilia infections, among hospitalized COVID-19 patients, leading the race of pathogens together with A.baumani [ 11 ]. S. maltophilia has also been recognized as a cause of outbreaks and pseudo-outbreaks, the latter being attributed to the colonization of bronchoscopic and other respiratory equipment by this microorganism [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%